Confirmed case of Pneumocystis pneumonia in a Maltese Terrier × Papillon dog being treated with toceranib phosphate. Issue 5 (25th April 2019) - Best, MP; Boyd, SP; Danesi, P
Abstract : Case report: A 7‐year‐old female‐neutered Maltese Terrier × Papillon dog was presented with tachypnoea and weight loss following 12 months of therapy with toceranib phosphate for a metastatic, histologically‐low‐grade mast cell tumour. The dog was diagnosed with Pneumocystis canis based on PCR with supportive clinical, radiographic and cytological findings. No other clinical evidence of immunocompromise was identified through assessment of haematology and immunoglobulin quantification. Clinical signs completely resolved with a short course of potentiated sulfonamides and discontinuation of the toceranib. Conclusion: To the authors' knowledge this represents the first case of Pneumocystis in a dog secondary to immunomodulatory drug therapy. It is also the first case of opportunist infection secondary to a tyrosine kinase inhibitor in dogs.